Parkinson’s disease quality of life at 12 months comparing invasive device-aided therapy with oral treatment - Adolfo Ramirez-Zamora; Michael S. Okun; Pavnit Kukreja; Wei Hu (npj Parkinson's Disease)
Abstract Real-world impact of device-aided therapy on quality of life (QoL) in people with Parkinson’s remains unknown. This large, retrospective, observational study assessed QoL in people transitioning to device-aided therapy (deep brain stimulation or carbidopa-levodopa enteral suspension) vs. those continuing oral medications. Cohorts were matched based on clinical/demographic characteristics and device-aided therapy eligibility. Primary and secondary outcomes included change from baseline (CFB) to month 12 in 39-item Parkinson’s Disease Questionnaire (PDQ-39) and Unified Parkinson’s Disease Rating Scale (UPDRS) scores, respectively. Of 608 people (oral therapy [n = 295]; device-aided therapy [n = 313]), most were male, White, and aged ≥ 60 years. Positive CFB to month 12 in PDQ-39 was significantly greater for device-aided therapy vs. oral therapy (–5.0 [95% CI, –5.9 to –4.2] vs. 0.9 [0.3–1.5]; p < 0.001). UPDRS II-IV scores improved for the device-aided therapy group. People transitioning to device-aided therapy experienced clinically meaningful QoL improvements.